Environmental Education in times of civilizatory crisis: curricular production in an Argentinian jurisdiction (Itinerarios Educativos, 2025)
This study analyses the incorporation of Environmental Education (EE) in the curriculum production of secondary education in Argentina, focusing on the province of Buenos Aires. It examines different levels of curriculum specification, from jurisdictional curriculum designs to teaching practices, and identifies the frequency of incorporation of environmental issues in them and the perspectives from which they are introduced. The study reveals that EA is integrated in a heterogeneous and fragmented manner in the Curriculum Designs, with important differences between Natural Science disciplines. Through the content analysis of the curricular designs and biographical interviews with teachers, it is evident that teachers are conditioned in the teaching of EA by the incorporation of the environment as content and by the organisational logic of the curricular designs, but also by their own school, work and social trajectories.
Keywords: Curriculum; Environmental Education; prescribed curriculum; teaching narratives